2023
DOI: 10.3390/cimb45050276
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Genetic Background of Osteosarcoma

Abstract: Osteosarcoma describes a tumor of mesenchymal origin with an annual incidence rate of four to five people per million. Even though chemotherapy treatment has shown success in non-metastatic osteosarcoma, metastatic disease still has a low survival rate of 20%. A targeted therapy approach is limited due to high heterogeneity of tumors, and different underlying mutations. In this review, we will summarize new advances obtained by new technologies, such as next generation sequencing and single-cell sequencing. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 126 publications
(154 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, the MSC-derived osteosarcoma cancer stem cells (O-CSC) can influence and promote tumorigenesis through intercellular communication and utility of growth factor containing vesicles, which, as a result, enhance recruitment of circulating MSCs that will aid in tumorigenesis [47]. The varying surrounding microenviroment acts as a supportive factor in further OS-CSC heterogeneity, where the exploitation of bone signaling allows the formation of niches (as illustrated by Abarrategi and colleagues in 2016) as the perivascular niche, the endosteal niche, and the hypoxic niche.…”
Section: Cancer Cell Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the MSC-derived osteosarcoma cancer stem cells (O-CSC) can influence and promote tumorigenesis through intercellular communication and utility of growth factor containing vesicles, which, as a result, enhance recruitment of circulating MSCs that will aid in tumorigenesis [47]. The varying surrounding microenviroment acts as a supportive factor in further OS-CSC heterogeneity, where the exploitation of bone signaling allows the formation of niches (as illustrated by Abarrategi and colleagues in 2016) as the perivascular niche, the endosteal niche, and the hypoxic niche.…”
Section: Cancer Cell Populationsmentioning
confidence: 99%
“…Whole genomic sequencing in pediatric patients in 2020 revealed that additional aberrant genomic modifications, such as chromosomal structural alterations secondary to chromothripsis, occurred in 20-89% of the patients, and 50-85% of patients have presented with kataegis that further promotes disease heterogeneity in OS [50]. This contributed to the formation of OS subclasses varying in morphology, metabolism, tumor microenvironment, immunogenicity, and metastatic potential, thus posing a challenge in evaluating the initial cause of osteosarcoma carcinogenesis [47]. Furthermore, deficiencies in DNA damage surveillance and repair also contributed to chromosomal structural abnormalities, deregulation of the tumor suppressor function, and uncontrolled cell cycle [41,43,51].…”
Section: Genomic Naturementioning
confidence: 99%
“…OS is not a uniform mass of cancer cells, but a complex, organ-like structure with diverse cell types influenced by various environmental factors [ 14 , 15 ]. An individual with OS is subject to a multitude of complex biological, structural, mechanical, and soluble factors that may affect the effectiveness of potential therapeutics [ 7 ].…”
Section: Advance In Os Cells and Modelsmentioning
confidence: 99%
“… 5 For recurrent diseases, surgical excision is superior to systemic therapy, while unresectable cases will be treated by systemic therapy or comprehensive therapy. 6 In addition, radiotherapy can help eliminate small or minimal residual tumors when substantial surgical resection is not feasible. 7 However, in most cases of osteosarcoma, radiotherapy is limited and its efficacy and indications are limited.…”
Section: Introductionmentioning
confidence: 99%